THE EFFICIENCY OF DYE-SENSITIZED SOLAR CELL (DSSC) IMPROVEMENT AS A LIGHT PARTY TiO2-NANO PARTICLE WITH EXTRACT PIGMENT MANGOSTANA PEEL (Garcinia Mangostana) WITH VARIOUS SOLVENTS (Jurnal Bahan Alam Terbarukan, 2018)
The dye-sensitized solar cell (DSSC) is one of the photochemical electrical cells consisting of a photoelectrode, dye, electrolyte, and counter electrode. The purpose of using dyes in the DSSC is to extend the absorption spectrum to visible light because visible light has about 96% energy from sunlight. This article presents some experimental data on the nature of absorbance and the conductivity of natural dyes extracted from the plant as an application in the DSSC. Absorbance test using Spectrophotometer UV Visible 1601 PC and electrical properties test using Elkahfi 100 / Meter I-V. DSSC fabrication has been done using dye extract of mangosteen skin pigment (Garcinia mangostana) with a variety of coating technique of Spin Coating and Slip Casting. The results show that natural dyes from natural material extraction have an absorbance spectrum of 380-520 nm range and the greatest conductivity is owned by mangosteen fruit skin pigment (Garcinia mangostana). From the results of the test using AM Simulator 1.5G (100 mW / cm2) diesel simulator, it was found that the volume of TiO2 precursors affected the performance of DSSC solar cells and the overall conversion efficiency was 0.084% for the mangosteen skin dye by slip casting technique and 0.092% for the mangosteen skin dye by spin coating technique.